Unlocking closed-loop recycling of spent LiFePO4 batteries via photocatalytic leaching: Efficient lithium recovery and mechanistic insights - Yinzhuang Fang; Shuya Chang; Yurong Han; Yifeng Han; Lina Jia; Mingyang Wu; Xianbao Wang; Rui Xia; Tao Mei (Chemical Engineering Journal, 2026)

Differential nutrient resorption strategies of soybean organs for adapting to climate warming - Mengya Chen; Pingting Guan; Wei Wang; Liang Chang; Ruslan Saifutdinov; Yurong Yang; Donghui Wu (Plant and Soil, 2026)

Moderate irrigation quotas enhance cotton growth in slightly saline soils by stabilizing the rhizosphere microbiome - Yurong Chang; Mingsi Li; Yulong Zhao; Dongwei Li; Shuai He (Irrigation Science, 2026)

Climate proofing maize through optimizing manure fertilization - Yurong Cai; Jianzheng Li; Naijie Chang; Ligang Wang; Heya Wei; Deli Chen; Frank Yonghong Li; Xia Liang (Journal of Cleaner Production, 2025)

Enhancing crop yield and carbon sequestration and greenhouse gas emission mitigation through different organic matter input in the Bohai Rim region: An estimation based on the DNDC-RF framework - Naijie Chang; Di Chen; Yurong Cai; Jianzheng Li; Mengxuan Zhang; Hu Li; Ligang Wang (Field Crops Research, 2024)

Efficient electron transport between NiO/Fe2O3 by loading amorphous carbon improves photocatalytic degradation property - Weihang Han; Jingxuan Shou; Shouxin Zhu; Xuewei Tu; Yutong Chen; Can Sun; Yurong Chang; Hui Zheng (Journal of Environmental Chemical Engineering, 2024)

Achieving high-rate and long-life Zn metal anodes via constructing interfacial gradient heterostructure - Yilun Ren; Biao Wang; Shaozhong Chang; Hao Wu; Yujie Ma; Fengqi Li; Cong Wang; Jian Gu; Yurong Yang; Shaochun Tang; Xiangkang Meng (Chemical Engineering Journal, 2024)

Efficient sunlight promoted nitrogen fixation from air under room temperature and ambient pressure via Ti/Mo composites - Liangchen Chen; Jingxuan Shou; Yutong Chen; Weihang Han; Xuewei Tu; Luping Zhang; Qiang Sun; Jun Cao; Yurong Chang; Hui Zheng (Chemical Engineering Journal, 2023)

miR-146a-3p suppressed the differentiation of hAMSCs into Schwann cells via inhibiting the expression of ERBB2 - Wei Chen; Linlin Ji; Zairong Wei; Chenglan Yang; Shusen Chang; Yucheng Zhang; Kaiyu Nie; Lingli Jiang; Yurong Deng (Cell and Tissue Research, 2021)
Human amniotic mesenchymal stem cells (hAMSCs) can be differentiated into Schwann-cell-like cells (SCLCs) in vitro. However, the underlying mechanism of cell differentiation remains unclear. In this study, we explored the phenotype and multipotency of hAMSCs, which were differentiated into SCLCs, and the expression of nerve repair-related Schwann markers, such as S100 calcium binding protein B (S-100), TNF receptor superfamily member 1B (P75), and glial fibrillary acidic protein (GFAP) were observed to be significantly increased. The secreted functional neurotrophic factors, like brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and neurotrophin-3 (NT-3), were determined and also increased with the differentiation time. Moreover, miR-146a-3p, which significantly decreased during the differentiation of hAMSCs into SCLCs, was selected by miRNA-sequence analysis. Further molecular mechanism studies showed that Erb-B2 receptor tyrosine kinase 2 (ERBB2) was an effective target of miR-146a-3p and that miR-146a-3p down-regulated ERBB2 expression by binding to the 3′-UTR of ERBB2. The expression of miR-146a-3p markedly decreased, while the mRNA levels of ERBB2 increased with the differentiation time. The results showed that down-regulating miR-146a-3p could promote SC lineage differentiation and suggested that miR-146a-3p negatively regulated the Schwann-like phenotype differentiation of hAMSCs by targeting ERBB2. The results will be helpful to establish a deeper understanding of the underlying mechanisms and find novel strategies for cell therapy.

On the relationships between the radial tidal current field and the radial sand ridges in the southern Yellow Sea: a numerical simulation - Yurong Zhu; Ruifang Chang (Geo-Marine Letters, 2001)